Governing higher education system as consumable goods for enhancing the employability of graduates in Ethiopia - Herut, Adane Hailu; Yimer, Berhanu Mekonnen; Demissie, Mesfin Molla; Bareke, Misganu Legesse; Agezew, Birhanu Haile; Dedho, Negash Haile; Lebeta, Mulugeta Fufa (Frontiers in Education, 2025)
The Ethiopian higher education system faces serious challenges in graduate employability, primarily due to a disconnect between academic curricula and labor market needs. Many graduates struggle to find meaningful employment, exacerbated by concerns over declining educational quality amid rapid institutional expansion. In light of these issues, this policy brief draws on findings from a 3-year research project titled “Education and Development in Ethiopia.” It emphasizes the urgent need for reforms in higher education, advocating for greater institutional autonomy, curriculum updates, inclusivity, and job-oriented programs that align with market demands. The brief aims to establish a structured policy framework for assessing educational outcomes, ultimately enhancing the quality of higher education in Ethiopia and better equipping graduates for success in the workforce.